Genome resequencing and comparative analysis of Streptococcus mutans in adults with high and low caries risk - Merve Yildirim Ucuncu; Musa Kazim Ucuncu; Ilker Karacan; Nursen Topcuoglu (Scientific Data)
Abstract Streptococcus mutans, is considered the main microbial etiological agent of dental caries, therefore it has been proposed as a useful predictor of caries risk as well as a target for caries prevention strategies. We aimed to compare the genomic characteristics of S. mutans strains isolated from individuals with high and low caries risk, in order to determine their genotypic features related to dental caries in adults. A total of 25 S. mutans isolates, obtained from the saliva of 13 volunteers with high dental caries activity and 12 caries-free individuals, were analysed using whole-genome sequencing techniques. A total of 2904 protein-coding gene sequences were detected as a result of the pan-genome analysis. The number of core genes detected in all genomes sequenced in the study was found to be 1563. A total of 50584 mutations were detected using ATCC 25175 strain as a reference. This is a large genome dataset of 25 S. mutans strains which can be further used for all S. mutans genome analysis.